Development Of A TOGAF-Based Target Operating Model For Enterprise Architecture: Integration Of Governance, IT Assets, IT Services, And Architect Competencies Through COBIT Alignment - Reza Irsyadul Ana; Rizki Sadewa (International Journal of Health Engineering and Technology, 2026)
Effective Enterprise Architecture (EA) practices require a framework that not only defines the architecture technically, but also integrates governance, IT asset management, IT services, and architect competencies into a structured ecosystem. This study proposes a TOGAF-based Enterprise Architecture Target Operating Model (TOM) linked to COBIT as an IT governance framework. The developed TOM encompasses five main dimensions: (1) the purpose of developing an architecture aligned with organizational strategy, (2) a comprehensive architectural landscape encompassing business, application, data, and technology domains, (3) the role and competencies of enterprise architects, (4) the role of the architecture board/committee in providing strategic direction, and (5) the linkage of the architecture cycle with the organizational budgeting cycle. Alignment between TOGAF and COBIT is built through mapping enterprise goals, alignment goals, and IT goals into EA processes, so that EA capabilities become measurable and auditable. This study uses a descriptive qualitative approach with a systematic literature review and framework analysis. The results of the study show that the integration of TOGAF-COBIT in TOM EA is able to increase the effectiveness of EA practices, ensure that the resulting architecture is aligned with the organization's strategic objectives, and strengthen overall IT governance.